Histoire récente de la forêt littorale du sud du Cameroun - Achille B. Biwolé; Olivier J. Hardy; Jean-Louis Doucet (Afriques)
Prior to the pre-colonial period in Central Africa, human populations were dispersed throughout the forests, where they engaged in slash-and-burn agriculture. Starting in the 19th century, they gradually established permanent settlements in villages, resulting in vast areas of abandoned forest. In present-day southern Cameroon, the forest canopy is primarily composed of large emergent trees, which are often attributed to past human activities. The aim of this study is to assess the significance of past human activities on the current floristic composition. Throughout the study area, there were shards of pottery, burnt palm nuts, and charcoal, indicating widespread human occupation and fire. This human occupation dates back to 2200 to 1500 BP, and more recently, three centuries ago. The frequent occurrence of fire and the presence of oil palm, both of recent origin, suggest the use of slash-and-burn agricultural practices. This coincides with the age of the large emergent trees and the dry climate phases recorded in the early 17th century. Therefore, these findings support the hypothesis that these activities have influenced the current floristic composition of the Central African forest.